The economic theory of organizations in the structure of modern economic theory - S. L. Sazanova; G. N. Ryazanova (Путеводитель предпринимателя, 2020)
The article reveals the features of the neoclassical economic theory of organizations and the institutional economic theory of organizations; the influence of the philosophy of modern and postmodern on the neoclassical and institutional economic theory of organizations is established, and the place and role of the economic theory of organizations in the structure of modern economic theory is determined.